2023
DOI: 10.3389/fbioe.2023.1187974
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma in the pathologic processes of tendinopathy: a review of basic science studies

Abstract: Tendinopathy is a medical condition that includes a spectrum of inflammatory and degenerative tendon changes caused by traumatic or overuse injuries. The pathological mechanism of tendinopathy has not been well defined, and no ideal treatment is currently available. Platelet-rich plasma (PRP) is an autologous whole blood derivative containing a variety of cytokines and other protein components. Various basic studies have found that PRP has the therapeutic potential to promote cell proliferation and differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 288 publications
0
2
0
Order By: Relevance
“…Nevertheless, the course of angiogenesis also has a major role during LET treatment. Proper angiogenesis is necessary during wound healing and regeneration; however, pathological neovascularization is one of the main characteristics of tendinopathy [26]. Research has shown that the PDGFRα homodimer promotes angiogenesis after binding with PDGF-AA and PDGF-CC [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the course of angiogenesis also has a major role during LET treatment. Proper angiogenesis is necessary during wound healing and regeneration; however, pathological neovascularization is one of the main characteristics of tendinopathy [26]. Research has shown that the PDGFRα homodimer promotes angiogenesis after binding with PDGF-AA and PDGF-CC [22].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it seems that the same processes that are involved in the treatment of tendinopathy also contribute to its development. The therapeutic effects of PRP in treating tendinopathy include stimulating cell proliferation, the synthesis of collagen, the regulation of angiogenesis, and modulation of inflammation [26]. The growth factors contained in PRP, including PDGFs, are responsible for the PRP's properties.…”
Section: Discussionmentioning
confidence: 99%
“…Wang Z (Wang et al, 2021) and Lee JS (Lee et al, 2022) et al have demonstrated that PRP is capable of promoting chondrogenic differentiation of stem cells, which is consistent with our own results. As the final therapeutic conclusion of HA and PRP for the treatment of OA is still undefined throughout so many basic research and preclinical studies (Zhang et al, 2022;Lu et al, 2023), this is a meaningful research direction not only in basic research, but also for future clinical research.…”
Section: Figurementioning
confidence: 99%
“…PRP contains various types of growth factors, inhibitors of inflammatory factors, and a rich fibrin network. Many of the ingredients synergistically participate in cell proliferation, growth, and differentiation, thereby regulating tissue repair, healing, and regeneration [11][12][13]. The number of primary studies in this area has increased substantially over the years [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%